Analisis Kritis Konsep Kurikulum Pendidikan Islam Indonesia di Sekolah (SD, SMP, SMA, & SMK) - Nur Hadi (Institut Agama Islam Tribakti Kediri, 2019)
Basically, every PAI curriculum development requires a clear and solid foundation, so that it is not easily swayed by the flow of transformation and innovation in education and learning that is so powerful as it has been lately. If the innovation, in general, tends to be top-down innovation through the power coercion strategy or coercion from the superiors in power. The change in curriculum from the KBK to KTSP is expected to be able to make Islamic religious education more able to make the quality of religious education more able to make changes in Indonesia. In addition to changing the morals of better students, it is hoped that it can also increase knowledge. In accordance with the objectives of the curriculum changes themselves who want to improve the quality of students, both intellectual, emotional and spiritual quality.